Implementasi Metode Amsilati dalam Mempermudah Membaca Kitab Kuning di Pondok Pesantren Al-Hikamusalafiyyah Cipulus Purwakarta - Dewi Silfa; Iwan Hermawan; Kasja Eki Waluyo (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
The Amtsilati method is a fast way to learn the yellow book. The Amtsilati method is inspired by the fast method of reading the Qur'an, namely the qiro'ati method. If in the qiro'ati method people can learn to read the Qur'an quickly, then with the Amtsilati method people will be able to read and understand bare books/books without harokat. This study aims to determine the effect of implementing the amtsilati method in making it easier to read the yellow book at the al-hikamusalafiyyah Islamic boarding school cipulus purwakarta. The method used by the author is quantitative, the data collection technique used is a questionnaire and observation. The results obtained from this study are based on the calculation of the slovin formula. The reality of using the amsilati method in the al-hikamussalafiyah Islamic boarding school cipulus purwakarta based on the data obtained an average value of 3,. The reality of using the amsilati method in the Islamic boarding school al-hikamussalafiyah cipulus purwakart, Based on the data obtained the average value of 3.1 this is included in the medium category, because it is between 2.5 - 3.5. The reality makes it easier to read the yellow ktab at the Islamic boarding school al-hikamussalafiyah cipulus purwakarta. Based on the data obtained, the average value of 3.1 is included in the medium category, because it is between 2.5 - 3.5. The effect of the amsilati method in making it easier to read the yellow book at the al-hikamussalafiyyah Islamic boarding school cipulus purwakarta after testing the data obtained then correlated between variables X and Y variables, there is a correlation of 0.75% (0.61-0.80) which shows a high correlation. Due to the influence of the use of the amtsilati method in making it easier to read the yellow book at the al-hikamusalafiyyah cipulus purwakarta Islamic boarding school, it is hoped that the pesantren will continue to strive for the implementation of learning using the amtsilati method to make it easier for students to read the yellow book, and teachers are expected to continue to look for games so that the use of the amtsilati method makes reading easier. the yellow book is more interesting and not monotonous